Successful language learning in a corporate setting: The role of attribution theory and its relation to intrinsic and extrinsic motivation - Kálmán, Csaba; Gutierrez Eugenio, Esther (Studies in Second Language Learning and Teaching, 2015)
Attribution theory (Weiner, 1985) and self-determination theory (Deci & Ryan, 1985) have been explored as contributors to L2 motivation (cf. Dörnyei, 2001) but have never been studied quantitatively in concert. In addition, students’ attributions for success in learning a foreign language have never been measured through the use of a questionnaire. The aim of this paper is therefore (a) to develop a questionnaire with reliable constructs that allows to measure adult learners’ attributions for their success in learning English in a corporate setting, (b) to investigate these learners’ attributions, and (c) to investigate the relationship between students’ attributions and the constructs of Intrinsic and Extrinsic motivation central to self-determination theory. Our main results show that among the attributions measured, interest, effort and corporate culture seemed to be the main causes that students recognised as directly involved in their success in learning English. Of all the attributional scales, interest and ability appeared to importantly contribute to intrinsic motivation, while corporate culture, encounters with foreign professionals and ability contributed to a lower extent to extrinsic motivation. It must be noted, however, that attributions for success to teacher and task were so consistently high that they could not be reliably measured with the questionnaire.